Innovations in information systems modeling : methods and best practices - Halpin, T. A.; Krogstie, John; Proper, Erik (Hershey, PA : Information Science Reference, 2009)
'This book presents cutting-edge research and analysis of the most recent advancements in the fields of database systems and software development'--Provided by publisher
'Premier reference source'--Cover
Includes bibliographical references (p. 315-346) and index
Keywords: System design; Database management; Computer software -- Development